(untitled) (Journal of Dhaka Medical College, 2010)
This prospective study was conducted in Dhaka Medical College Hospital during July 2006 to June 2007. 100 patients were included in the study among which forty seven received benzylpenicillin and fifty three was treated with ceftriaxone. The result of this study showed that mortality was similar in both groups but ceftriaxone had better outcome regarding duration of clinical features and hospital-stay. Key words: pyogenic meningitis; benzylpenicillin; ceftriaxone. DOI: 10.3329/jdmc.v17i2.6583 J Dhaka Med Coll. 2008; 17(2) : 59-61